Electrode for ozone generation

By installing a catalyst layer composed of tin oxide, antimony oxide and nickel oxide on the titanium or titanium alloy electrode matrix and performing heat treatment, the problem of unstable ozone generation in neutral aqueous solution is solved, and an efficient and durable ozone generation effect is achieved.

CN119421971APending Publication Date: 2025-02-11ISHIFUKU METAL IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380048918.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-27
Filing Date
2023-06-21
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art is difficult to stably generate ozone in neutral aqueous solutions, and the ozone generation efficiency and durability are insufficient.

Method used

An electrode matrix made of titanium or titanium alloy is used, and a catalyst layer composed of tin oxide, antimony oxide and nickel oxide are provided on its surface. The electric double layer capacitance is formed by heat treatment to improve ozone generation efficiency and durability.

Benefits of technology

The ozone generation efficiency is significantly improved in neutral aqueous solutions, and the durability of the electrode is enhanced, so that ozone can be generated stably in urban water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201197800000111
    Figure BDA0005201197800000111
Patent Text Reader

Abstract

The purpose of the present invention is to provide an electrode for ozone generation, which has excellent ozone generation efficiency and excellent durability even in a neutral aqueous solution such as urban water. The electrode for ozone generation according to the present invention is an electrode for electrolysis and comprises an electrode base made of titanium or a titanium alloy, and a catalyst layer provided on the electrode base, the catalyst layer comprises, in terms of metal, 79.0 mol% to 90.0 mol% of tin oxide, 7.0 mol% to 17.0 mol% of antimony oxide, and 0.1 mol% or more than 0.1 mol% to 6.0 mol% of nickel oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an ozone generating electrode for generating ozone water. Background Art

[0002] Hypochlorous acid sterilizing water using chlorine generated by electrolysis of water is used in many fields. However, depending on the region, there is a problem that city water does not contain chlorine and salt must be added before electrolysis. Therefore, ozone water using ozone has attracted attention as a substance with stronger sterilizing power than hypochlorous acid. The methods of generating ozone water are now roughly divided into two categories. One is a method of generating ozone by discharge such as silent discharge, and then dissolving it in water to obtain ozone water. The other is a method of obtaining ozone water by electrolyzing water and dissolving the ozone generated in the anode reaction in water as an electrolyte.

[0003] In the former case, there is a problem that ozone in the gas phase is difficult to dissolve in water and concentration adjustment is difficult. On the other hand, in the latter case, ozone water can be directly generated by electrolysis, and concentration adjustment can be easily performed according to electrolysis conditions.

[0004] Regarding the method of electrolyzing water, Non-Patent Document 1 discloses that ozone is generated by electrolysis in an acidic sulfuric acid aqueous solution using a platinum wire electrode as an anode.

[0005] Prior art literature

[0006] Non-patent literature

[0007] Non-patent document 1: Electrochemistry and Industrial Physical Chemistry (Electrochemistry and Industrial Physical Chemistry), 54(10), p890-895, 1986 Summary of the invention

[0008] Technical Problems to be Solved by the Invention

[0009] The method of Non-Patent Document 1 uses an acidic sulfuric acid aqueous solution as an electrolyte. Therefore, there is a strong demand for an electrode that stably generates ozone in a neutral aqueous solution such as city water that is easier to handle than sulfuric acid.

[0010] An object of the present invention is to provide an ozone generating electrode having excellent ozone generation efficiency and excellent durability even in a neutral aqueous solution such as city water.

[0011] Solutions for solving technical problems

[0012] The present inventors discovered that by providing a catalyst layer on a substrate made of titanium or a titanium alloy (the catalyst layer is composed of 79.0 mol% to 90.0 mol% of tin oxide, 7.0 mol% to 17.0 mol% of antimony oxide, and 0.1 mol% or more than 0.1 mol% to 6.0 mol% of nickel oxide in terms of metal conversion), an electrode with high ozone generation efficiency and excellent durability in urban water can be obtained, thereby completing the present invention.

[0013] That is, the above-mentioned object is achieved by an ozone generating electrode, characterized in that the electrolysis electrode comprises:

[0014] an electrode substrate made of titanium or a titanium alloy, and

[0015] The catalyst layer is arranged on the electrode substrate, and the catalyst layer is composed of 79.0 mol% to 90.0 mol% of tin oxide, 7.0 mol% to 17.0 mol% of antimony oxide, and 0.1 mol% or more than 0.1 mol% to 6.0 mol% of nickel oxide in terms of metal conversion.

[0016] The double-layer capacitance of the ozone generating electrode is 2 to 40 (mC / cm 2 ).

[0017] In addition, the above-mentioned object can be achieved by a method for producing an ozone generating electrode, characterized in that:

[0018] A solution in which tin oxide particles and antimony oxide particles are dispersed in a lower alcohol and a solution in which a nickel compound is dissolved in a lower alcohol are mixed, the mixed solution is applied to a titanium substrate and dried, and then heat treated at 300° C. to 700° C. in the atmosphere.

[0019] According to the present invention, it is possible to provide an ozone generating electrode which has excellent ozone generation efficiency even in a neutral aqueous solution such as city water and excellent durability. DETAILED DESCRIPTION

[0020] The present invention is an electrode for generating ozone, characterized in that it comprises:

[0021] an electrode substrate made of titanium or a titanium alloy, and

[0022] The catalyst layer disposed on the electrode substrate is composed of 79.0 mol% to 90.0 mol% of tin oxide, 7.0 mol% to 17.0 mol% of antimony oxide, and 0.1 mol% or more to 6.0 mol% of nickel oxide in terms of metal.

[0023] In addition, the manufacturing method of the ozone generating electrode of the present invention is characterized in that a solution obtained by dispersing tin oxide particles and antimony oxide particles in a lower alcohol and a solution obtained by dissolving a nickel compound in a lower alcohol are mixed, the mixed solution is applied to a titanium substrate and dried, and then the applied and dried titanium substrate is heat treated at 300°C to 700°C in the atmosphere.

[0024] In the above embodiment, a solution in which tin oxide microparticles are dispersed in a lower alcohol, a solution in which antimony oxide microparticles are dispersed in a lower alcohol, and a solution in which a nickel compound is dissolved in a lower alcohol may be mixed to prepare a mixed solution.

[0025] Alternatively, the mixed solution may be degreased, applied to a titanium substrate roughened with an acid, and dried, and then the applied and dried titanium substrate may be heat treated at 300° C. to 700° C. in the atmosphere.

[0026] Hereinafter, the ozone generating electrode and the method for producing the same according to the present invention will be described.

[0027] <Electrode substrate>

[0028] As the material of the electrode substrate used in the present invention, titanium or titanium-based alloy can be cited. As titanium-based alloy, an alloy with corrosion resistance and electrical conductivity based on titanium is used, for example, a Ti-based alloy usually used as an electrode material and formed by a combination of Ti-Ta-Nb, Ti-Zr, Ti-Al, etc. can be cited. These electrode materials can be processed into desired shapes such as plate-like, perforated plate-like, rod-like, mesh-like, and used as electrode substrates.

[0029] <Pretreatment of electrode substrate>

[0030] As mentioned above, for the electrode substrate, it is preferred to pre-treat it in advance as is usually done. As a preferred specific example of such pre-treatment, the following treatment can be cited. First, according to conventional methods, the surface of the electrode substrate (hereinafter sometimes referred to as "titanium substrate") made of the above-mentioned titanium or titanium-based alloy is cleaned with, for example, alcohol, acetone, etc. and / or degreased by electrolysis in an alkaline solution, and then treated with hydrofluoric acid having a hydrogen fluoride concentration of 1 to 20% by weight, or a mixed acid of hydrofluoric acid and other acids such as nitric acid and sulfuric acid, thereby removing the oxide film on the surface of the titanium substrate and roughening the titanium grain boundary unit. The acid treatment can be carried out at a temperature of room temperature to about 40°C for several minutes to more than ten minutes depending on the surface state of the titanium substrate. It should be noted that in order to fully carry out the roughening, sandblasting can also be used in combination.

[0031] <Titanium hydride treatment>

[0032] The surface of the titanium substrate treated with acid is brought into contact with concentrated sulfuric acid, so that the internal surface of the titanium grain boundary is finely roughened into a protrusion, and a thin layer of titanium hydride is formed on the surface of the titanium substrate. The concentrated sulfuric acid used is generally 40 to 80% by weight, preferably 50 to 60% by weight. As needed, in order to stabilize the treatment, a small amount of sodium sulfate, other sulfates, etc. can be added to the concentrated sulfuric acid. The contact with the concentrated sulfuric acid can usually be carried out by immersing the titanium substrate in a concentrated sulfuric acid bath, and the bath temperature at this time is generally about 100°C to about 150°C, preferably a temperature in the range of about 110°C to about 130°C. In addition, the immersion time is usually about 0.5 minutes to about 10 minutes, preferably about 1 minute to about 3 minutes. Through the sulfuric acid treatment, the internal surface of the titanium grain boundary can be finely roughened into a protrusion, and a very thin titanium hydride coating is formed on the surface of the titanium substrate. The titanium substrate treated with sulfuric acid is taken out from the sulfuric acid bath and preferably rapidly cooled in an inert gas atmosphere such as nitrogen or argon to reduce the surface temperature of the titanium substrate to below about 60° C. For such rapid cooling, it is preferable to use a large amount of cold water for simultaneous washing.

[0033] In this way, the titanium substrate with a very thin titanium hydride coating layer formed on the surface is immersed in dilute hydrofluoric acid or dilute fluoride aqueous solution (such as sodium fluoride, potassium fluoride, etc.) to grow the titanium hydride coating and achieve uniformity and stabilization of the coating. The concentration of hydrogen fluoride in the dilute hydrofluoric acid or dilute fluoride aqueous solution that can be used here can generally be in the range of 0.05 to 3% by weight, preferably in the range of 0.3 to 1% by weight. In addition, the temperature when using these solutions for immersion treatment is generally 10°C to 40°C, preferably 20°C to 30°C. The treatment can be carried out until a uniform titanium hydride coating with a thickness of generally 0.5 to 10 microns, preferably 1 to 3 microns, is formed on the surface of the titanium substrate. Since the titanium hydride (TiHy, where y is a number of 1.5 to 2) presents a color ranging from gray-brown to dark brown according to the degree of hydrogenation, the generation of the titanium hydride coating with the above-mentioned range of thickness can control the color tone change of the substrate surface by comparing the brightness with the standard color source from experience.

[0034] <Formation of Catalyst Layer>

[0035] Then, on the above-mentioned pretreated titanium substrate, a mixed liquid (a mixed liquid obtained by mixing a solution obtained by dispersing tin oxide particles and antimony oxide particles in a lower alcohol and a solution obtained by dissolving a nickel compound in a lower alcohol) is applied on the titanium substrate and dried, and heat-treated (fired) to form a catalyst layer composed of tin oxide, antimony oxide and nickel oxide.

[0036] In the above embodiment, a solution in which tin oxide microparticles are dispersed in a lower alcohol, a solution in which antimony oxide microparticles are dispersed in a lower alcohol, and a solution in which a nickel compound is dissolved in a lower alcohol may be mixed to prepare a mixed solution.

[0037] As the solvent of the above solution, a lower alcohol is preferred, and methanol, ethanol, propanol, butanol, isobutanol or a mixture thereof can be advantageously used. In addition, in the case of containing fine tin oxide particles and fine antimony oxide particles, a dispersant can also be added. As the dispersant, acetylacetone, alkyl ether carboxylic acid, etc. can be used.

[0038] The total metal concentration of the tin compound, antimony compound and nickel compound in the low-grade alcohol solution can generally be in the range of 20 to 300 g / L, preferably 40 to 290 g / L. When the metal concentration is lower than 20 g / L, the catalyst loading efficiency deteriorates, and when it exceeds 300 g / L, the catalyst is easily segregated, resulting in problems such as catalyst activity, adhesion strength, and uneven loading.

[0039] The substrate coated with the above solution on the titanium surface is dried at a temperature within the range of about 20°C to about 150°C as required, and then heat treated in an oxygen-containing gas atmosphere, for example, in air. Heat treatment can be carried out in the following manner: in a suitable heating furnace such as an electric furnace, a gas furnace, an infrared furnace, etc., it is heated to a temperature (below 700°C) at which each metal compound is usually decomposed, each metal forms a stable oxide, and the oxidation of the titanium substrate does not grow too thick. The heating time depends on the size of the substrate to be heat treated, and can be roughly set to about 3 minutes to 30 minutes. Through this heat treatment, a metal oxide composed of tin oxide, antimony oxide, and nickel oxide can be formed and loaded on the surface of titanium.

[0040] Furthermore, when a sufficient amount of the metal oxide composed of tin oxide, antimony oxide and nickel oxide cannot be formed and supported by a single supporting operation, the steps of applying the solution, drying and heat treatment may be repeated as many times as desired.

[0041] In the catalyst layer composed of tin oxide, antimony oxide and nickel oxide, the proportion of each component is 79.0 mol% to 90.0 mol% of tin oxide, 7.0 mol% to 17.0 mol% of antimony oxide, and 0.1 mol% or more than 0.1 mol% to 6.0 mol% of nickel oxide in terms of metal conversion. In addition, the total proportion of each component is 100%.

[0042] Here, as another embodiment, the ratio of the tin oxide may be more than 79.0 mol% to less than 90.0 mol% in terms of metal conversion. In addition, as another embodiment, it may be 80.0 mol% to 89.7 mol% in terms of metal conversion. In addition, as another embodiment, the ratio of the tin oxide may be 81.0 mol% to 89.5 mol% in terms of metal conversion. In addition, as another embodiment, the ratio of the tin oxide may be 82.0 mol% to 89.0 mol% in terms of metal conversion. When the ratio of the tin oxide is less than 79.0 mol% or exceeds 90.0 mol%, the durability of the catalyst layer becomes insufficient.

[0043] In addition, as another embodiment, the ratio of the antimony oxide may be 7.6 mol% to 16.0 mol% in terms of metal. In addition, as another embodiment, the ratio of the antimony oxide may be 8.0 mol% to 15.0 mol% in terms of metal. When the ratio of the antimony oxide is less than 7.0 mol% or exceeds 17.0 mol%, the durability of the catalyst layer becomes insufficient.

[0044] Furthermore, as another embodiment, the ratio of the nickel oxide may be 0.2 mol% to 5.5 mol% in terms of metal. In addition, as another embodiment, the ratio of the nickel oxide may be 0.4 mol% to 2 mol% in terms of metal. When the ratio of the nickel oxide is less than 0.1 mol% or exceeds 6.0 mol%, the durability of the catalyst layer becomes insufficient.

[0045] In the manufacturing method of the present invention, a solution in which fine tin oxide particles and fine antimony oxide particles are dispersed, or a solution in which fine tin oxide particles are dispersed in a lower alcohol and a solution in which fine antimony oxide particles are dispersed in a lower alcohol are used, applied and dried, and then heat-treated to obtain a catalyst layer. The average particle size of the tin oxide particles and antimony oxide particles used here is 10nm to 300nm, preferably 40nm to 150nm.

[0046] The double-layer capacitance of the ozone generating electrode of the present invention is 2 to 40 (mC / cm 2 ).

[0047] In the method for manufacturing an ozone generating electrode of the present invention, a solution obtained by dispersing tin oxide particles and antimony oxide particles in a lower alcohol (or a solution obtained by dispersing tin oxide particles in a lower alcohol and a solution obtained by dispersing antimony oxide particles in a lower alcohol) and a solution obtained by dissolving a nickel compound in a lower alcohol are mixed, and the mixed solution is applied to a titanium substrate and dried. The titanium substrate after application and drying is then heat-treated at 300°C to 700°C in the atmosphere. If the number of application, drying, and heat-treatment steps of the solution is increased to thicken the catalyst layer, the double-layer capacitance is also increased. By setting the number of the above-mentioned application, drying, and heat-treatment steps to a few to about 20 layers, the value of the double-layer capacitance can be set to 2 to 40 (mC / cm 2 ).

[0048] It should be noted that, in order to make the above catalyst layer more stable, a post-treatment step of 2 to 20 hours at 500°C to 700°C in the atmosphere may be added. The treatment time may also be 4 to 18 hours. For example, the post-treatment may be performed at 550°C in the atmosphere for 16 hours.

[0049] The value of the double-layer capacitance of the ozone generating electrode of the present invention is preferably 3 to 30 (mC / cm 2 ).

[0050] The electrode produced by the production method of the present invention is characterized in that the electric double layer capacitance is very large.

[0051] (1) It is believed that the double-layer capacitance is positively correlated with the surface area of ​​the electrode. The larger the double-layer capacitance of the electrode, the larger the surface area of ​​the catalyst layer.

[0052] (2) When the double-layer capacitance is large, that is, the surface area of ​​the catalyst layer is large, the utilization rate of the catalyst will increase. It is speculated that as the utilization rate of the catalyst increases, many catalyst active points participate in the reaction, so the activity increases, the load per unit area decreases, and the durability also increases.

[0053] Example

[0054] The present invention is specifically described by way of examples, but the present invention is not limited to these examples.

[0055] [Example 1]

[0056] 0.012 g of ethanol solution of nickel (II) chloride hexahydrate (Ni concentration = 46 g / kg) was added to 1 g of isobutyl alcohol solution (Sn concentration = 197 g / kg, Sb concentration = 32 g / kg) in which tin dioxide particles and antimony pentoxide particles were dispersed, and 31 kHz ultrasonic waves were irradiated for 10 minutes to prepare a coating liquid. The average particle size of the tin dioxide particles and antimony pentoxide particles in the butanol solution used here was measured with a laser diffraction / scattering particle size distribution measuring device, and the result was 146 nm.

[0057] Next, a titanium plate (t 0.5 mm × 100 mm × 50 mm) equivalent to JIS grade 1 was immersed in acetone, ultrasonically cleaned for 10 minutes for degreasing, and then treated in 8 wt % hydrofluoric acid at 20° C. for 1 minute, and then treated in 60 wt % sulfuric acid aqueous solution at 120° C. for 1 minute. The titanium substrate was then treated in 0.3 wt % hydrofluoric acid at 20° C. for 45 seconds.

[0058] 0.13 mL of the coating solution was applied to the surface-treated titanium substrate, dried at room temperature for 5 minutes, and then treated at 550° C. for 5 minutes in the air.

[0059] The above steps were repeated 6 times to produce the electrode of Example 1, in which a metal oxide composed of 86.0 mol % of tin oxide, 13.5 mol % of antimony oxide and 0.5 mol % of nickel oxide (calculated as metal) was supported on the titanium substrate.

[0060] [Example 2]

[0061] The electrode of Example 2 was prepared in the same manner as Example 1, except that the amount of added nickel (II) chloride hexahydrate ethanol solution (Ni concentration = 46 g / kg) was changed to 0.023 g, wherein a metal oxide composed of 85.6 mol % of tin oxide, 13.5 mol % of antimony oxide, and 0.9 mol % of nickel oxide was loaded on a titanium substrate (calculated as metal).

[0062] [Example 3]

[0063] The electrode of Example 3 was prepared in the same manner as Example 1, except that the amount of added nickel (II) chloride hexahydrate ethanol solution (Ni concentration = 46 g / kg) was changed to 0.047 g. In this case, a metal oxide (calculated as metal) consisting of 84.7 mol % tin oxide, 13.4 mol % antimony oxide, and 1.9 mol % nickel oxide was loaded on a titanium substrate.

[0064] [Example 4]

[0065] The electrode of Example 4 was prepared in the same manner as Example 1, except that the amount of added nickel (II) chloride hexahydrate ethanol solution (Ni concentration = 46 g / kg) was changed to 0.071 g, wherein a metal oxide composed of 83.9 mol % of tin oxide, 13.3 mol % of antimony oxide, and 2.8 mol % of nickel oxide (calculated as metal) was loaded on a titanium substrate.

[0066] [Example 5]

[0067] The electrode of Example 5 was prepared in the same manner as Example 1, except that the amount of added nickel (II) chloride hexahydrate ethanol solution (Ni concentration = 46 g / kg) was changed to 0.096 g, wherein a metal oxide composed of 83.0 mol % of tin oxide, 13.2 mol % of antimony oxide, and 3.8 mol % of nickel oxide (calculated as metal) was loaded on a titanium substrate.

[0068] [Example 6]

[0069] 0.062 g of ethanol solution of nickel (II) chloride hexahydrate (Ni concentration = 46 g / kg) was added to 1 g of an isobutyl alcohol solution (Sn concentration = 256 g / kg, Sb concentration = 27 g / kg) in which tin dioxide particles and antimony pentoxide particles were dispersed, and 31 kHz ultrasonic waves were irradiated for 10 minutes to prepare a coating liquid. The average particle size of the tin dioxide particles and antimony pentoxide particles in the butanol solution used here was measured using a laser diffraction / scattering particle size distribution measuring device, and the result was 146 nm.

[0070] Next, a titanium plate (t 0.5 mm × 100 mm × 50 mm) equivalent to JIS grade 1 was immersed in acetone, ultrasonically cleaned for 10 minutes for degreasing, treated in 8 wt % hydrofluoric acid at 20° C. for 1 minute, and then treated in 60 wt % sulfuric acid aqueous solution at 120° C. for 1 minute. Next, the titanium substrate was treated in 0.3 wt % hydrofluoric acid at 20° C. for 45 seconds.

[0071] 0.13 mL of the coating solution was applied to the surface-treated titanium substrate, dried at room temperature for 5 minutes, and then treated at 550° C. for 5 minutes in the air.

[0072] The above process was repeated 6 times, and as the final post-treatment process, the electrode was treated in the atmosphere at 550°C for 16 hours to produce the electrode of Example 6, in which a metal oxide composed of 88.9 mol % of tin oxide, 9.1 mol % of antimony oxide, and 2.0 mol % of nickel oxide (calculated as metal) was loaded on the titanium substrate.

[0073] [Example 7]

[0074] The electrode of Example 7 was prepared in the same manner as Example 6, except that the amount of added nickel (II) chloride hexahydrate ethanol solution (Ni concentration = 46 g / kg) was changed to 0.159 g. In this case, a metal oxide (calculated as metal) consisting of 86.2 mol % of tin oxide, 8.8 mol % of antimony oxide, and 5.0 mol % of nickel oxide was loaded on a titanium substrate.

[0075] [Example 8]

[0076] The electrode of Example 8 was prepared in the same manner as Example 6, except that the coating and firing steps were repeated 21 times, wherein a metal oxide composed of 88.9 mol % of tin oxide, 9.1 mol % of antimony oxide, and 2.0 mol % of nickel oxide was loaded on a titanium substrate (calculated as metal).

[0077] [Example 9]

[0078] The electrode of Example 9 was prepared in the same manner as Example 6 except that the temperature of the post-treatment step was 650°C, wherein a metal oxide composed of 88.9 mol % of tin oxide, 9.1 mol % of antimony oxide, and 2.0 mol % of nickel oxide (calculated as metal) was loaded on a titanium substrate.

[0079] [Comparative Example 1]

[0080] A JIS1 grade titanium plate (t 0.5mm×100mm×100mm) was immersed in acetone, ultrasonically cleaned for 10 minutes for degreasing, and then treated in 8 wt% hydrofluoric acid at 20°C for 2 minutes, followed by treatment in a 60 wt% sulfuric acid aqueous solution at 120°C for 3 minutes. Next, the titanium substrate was taken out from the sulfuric acid aqueous solution, sprayed with cold water in a nitrogen atmosphere and rapidly cooled. It was further immersed in a 0.3 wt% hydrofluoric acid aqueous solution at 20°C for 2 minutes and then rinsed with water. After the titanium substrate was rinsed with water, dinitrodiammineplatinum was dissolved in a sulfuric acid solution and electroplated in a platinum plating bath adjusted to a platinum content of 5g / L, pH≈2, and 50°C to produce a load of 6.5mg / cm 2 The electrode of Comparative Example 1 was made of platinum.

[0081] [Comparative Example 2]

[0082] A coating liquid was prepared by adding 14.770 g of tin (IV) chloride pentahydrate, 0.620 g of antimony (III) oxide, and 0.107 g of nickel (II) chloride hexahydrate to 34.5 g of ethanol and stirring the mixture.

[0083] Next, a titanium plate (t 0.5 mm × 100 mm × 100 mm) equivalent to JIS grade 1 was immersed in acetone, ultrasonically cleaned for 10 minutes for degreasing, and then treated in 8 wt % hydrofluoric acid at 20° C. for 1 minute, and then treated in 60 wt % sulfuric acid aqueous solution at 120° C. for 1 minute. Next, the titanium substrate was treated in 0.3 wt % hydrofluoric acid at 20° C. for 45 seconds.

[0084] 0.24 mL of the coating solution was applied onto the surface-treated titanium substrate, dried at room temperature for 10 minutes, and then treated at 550° C. for 10 minutes in the air.

[0085] The above steps were repeated 14 times to prepare the electrode of Comparative Example 2, in which a metal oxide composed of 93.0 mol % of tin oxide, 6.0 mol % of antimony oxide, and 1.0 mol % of nickel oxide (calculated as metal) was supported on the titanium substrate.

[0086] [Comparative Example 3]

[0087] 0.009 g of ethanol solution of nickel (II) chloride hexahydrate (Ni concentration = 46 g / kg) was added to 1 g of an isobutyl alcohol solution (Sn concentration = 256 g / kg, Sb concentration = 27 g / kg) in which tin dioxide particles and antimony pentoxide particles were dispersed, and 31 kHz ultrasonic waves were irradiated for 10 minutes to prepare a coating liquid. The average particle size of the tin dioxide particles and antimony pentoxide particles in the butanol solution used here was measured using a laser diffraction / scattering particle size distribution measuring device, and the result was 146 nm.

[0088] Next, a titanium plate (t 0.5 mm × 100 mm × 50 mm) equivalent to JIS grade 1 was immersed in acetone, ultrasonically cleaned for 10 minutes for degreasing, and then treated in 8 wt % hydrofluoric acid at 20° C. for 1 minute, and then treated in 60 wt % sulfuric acid aqueous solution at 120° C. for 1 minute. Next, the titanium substrate was treated in 0.3 wt % hydrofluoric acid at 20° C. for 45 seconds.

[0089] 0.13 mL of the coating solution was applied to the surface-treated titanium substrate, dried at room temperature for 5 minutes, and then treated at 550° C. for 5 minutes in the air.

[0090] The above process was repeated 6 times without post-treatment to produce the electrode of Comparative Example 3, in which a metal oxide composed of 90.5 mol % tin oxide, 9.2 mol % antimony oxide and 0.3 mol % nickel oxide (calculated as metal) was loaded on the titanium substrate.

[0091] <Ozone generation efficiency>

[0092] Using Examples 1 to 5 and Comparative Examples 1 to 2 as anodes, electrolysis was performed under the following conditions to determine the ozone generation efficiency. The electrolyte used was 150 ml of an aqueous solution containing 0.25 mmol of MgSO4, 0.25 mmol of NaHCO3, 0.25 mmol of CaCl2, and 0.025 mmol of KHCO3 per liter. Then, a current density of 2 A / dm 2 Electrolysis was performed for 120 seconds with constant current control. Afterwards, the ozone generation amount was obtained using the indigo method and the ozone generation efficiency was calculated.

[0093] <Durability test>

[0094] Using the electrodes of Examples 1 to 5 and Comparative Examples 1 to 2 as anodes, a durability test was conducted under the following conditions, and the ozone generation efficiency of Examples 1 to 5 and Comparative Examples 1 to 2 before and during the durability test was determined by the above method. The results are shown in Table 1.

[0095] The electrolyte used was 150 ml of an aqueous solution containing 0.25 mmol of MgSO4, 0.25 mmol of NaHCO3, 0.25 mmol of CaCl2, and 0.025 mmol of KHCO3 in 1 L. Then, a current density of 2 A / dm 2 Electrolysis is carried out under constant current control.

[0096] <Measurement method of electric double layer capacitance>

[0097] A three-electrode electrolytic cell was used to perform CV (cyclic voltammetry) measurements, and the double-layer capacitance was determined from the obtained cyclic voltammogram. Specifically, the electrodes (20×25 mm) of the embodiments and comparative examples were used as working electrodes, silver-silver chloride electrodes were used as reference electrodes, and Pt plates were used as counter electrodes. CV measurements were performed in 0.5 M sulfuric acid at a potential range of 0.8 to 1.3 V (relative to Ag / AgCl) and a scan rate of 50 mV / s. Calculate 1 / 2 of the sum of the charge and discharge quantities of the obtained double-layer capacitance and divide it by the electrode area of ​​5 cm 2 , as the double-layer capacitance of the above electrode. The obtained double-layer capacitance (mC / cm 2 ) are recorded in Table 1.

[0098] [Table 1]

[0099]

Claims

1. An ozone generating electrode, characterized in that: It contains: an electrode substrate made of titanium or a titanium alloy, and The catalyst layer is arranged on the electrode substrate, and the catalyst layer is composed of 79.0 mol% to 90.0 mol% of tin oxide, 7.0 mol% to 17.0 mol% of antimony oxide, and 0.1 mol% or more than 0.1 mol% to 6.0 mol% of nickel oxide in terms of metal conversion.

2. The ozone generating electrode according to claim 1, characterized in that: The double layer capacitance is 2 to 40 (mC / cm 2 ).

3. The method for producing an ozone generating electrode according to claim 1 or 2, characterized in that: A solution in which tin oxide particles and antimony oxide particles are dispersed in a lower alcohol and a solution in which a nickel compound is dissolved in a lower alcohol are mixed, the mixed solution is applied to a titanium substrate and dried, and then heat treated at 300° C. to 700° C. in the atmosphere.